2021
DOI: 10.3390/microorganisms9081593
|View full text |Cite
|
Sign up to set email alerts
|

Glucosidase Inhibitors Screening in Microalgae and Cyanobacteria Isolated from the Amazon and Proteomic Analysis of Inhibitor Producing Synechococcus sp. GFB01

Abstract: Microalgae and cyanobacteria are good sources for prospecting metabolites of biotechnological interest, including glucosidase inhibitors. These inhibitors act on enzymes related to various biochemical processes; they are involved in metabolic diseases, such as diabetes and Gaucher disease, tumors and viral infections, thus, they are interesting hubs for the development of new drugs and therapies. In this work, the screening of 63 environmental samples collected in the Brazilian Amazon found activity against β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 126 publications
1
4
0
1
Order By: Relevance
“…In this study, the ethanolic extract of Leptolyngbya sp. KC45 inhibited the α-glucosidase enzyme with a IC 50 value of 5.47 mg/mL (207.24 mg-AE/g-extract) ( Figure 3 ), which is in line with the extracts (IC 50 = 0.01–50 mg/mL) from black legumes [ 123 ], shmar ( Arbutus pavarii Pamp) [ 124 ], guarana [ 125 ], and algae [ 126 ]. The high inhibitory activity against the α-glucosidase enzyme may be due to the high concentration and variety of phenolic chemicals found in the extract.…”
Section: Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…In this study, the ethanolic extract of Leptolyngbya sp. KC45 inhibited the α-glucosidase enzyme with a IC 50 value of 5.47 mg/mL (207.24 mg-AE/g-extract) ( Figure 3 ), which is in line with the extracts (IC 50 = 0.01–50 mg/mL) from black legumes [ 123 ], shmar ( Arbutus pavarii Pamp) [ 124 ], guarana [ 125 ], and algae [ 126 ]. The high inhibitory activity against the α-glucosidase enzyme may be due to the high concentration and variety of phenolic chemicals found in the extract.…”
Section: Resultssupporting
confidence: 69%
“…Similarly, along with their powerful antioxidant action, phenolic-rich samples have been shown to have a high potential for suppressing the activity of the α-glucosidase enzyme [ 124 ]. In addition, several studies have demonstrated that phytochemicals from plants and algae might be a rich natural supply of phenolic and flavonoid compounds, which are well-known for their significant hypoglycemic potential [ 126 , 127 ]. It is important to point out that the ethanolic extract obtained from Leptolyngbya sp.…”
Section: Resultsmentioning
confidence: 99%
“…A study comparing glucosidase inhibition among microalgae species isolated from the Amazon revealed that Synechococcus sp. had one of the highest glucosidase inhibitions, thus emerging as a potential anti-diabetic supplement [ 134 ]. In that context, the highest concentration of Synechococcus sp.…”
Section: Effect Of Microalgae On Diabetes Mellitusmentioning
confidence: 99%
“…Some bioproducts of cyanobacteria are dependent on the limitations of one or more nutrients [ 307 , 308 , 309 , 310 , 311 ]. For instance, the Scyto accumulation in S. ocellatum ATCC 55232 noticeably varies depending on the growing medium.…”
Section: Regulationmentioning
confidence: 99%